(untitled) (Physical Education, Health and Social Sciences, 2025)
The primary objective of the current study was to develop and then assess Piroxicam ointment with penetration enhancers, including castor oil, thymus oil, and clove oil. As per B. P., 4.750 g of hard paraffin was melted at sixty degrees Celsius, and then 4.75 g of Cetostearyl alcohol, 4.75 g wool fat was added to create the 0.5% formulations of Piroxicam salt ointment was mix in it. Following the addition of 82.25 g of soft paraffin, , and 3 ml of each of the following oils, such as thymol, clove, and castor, were added, first separately and then all at once, while stirring constantly. At last, the room temperature was reached by letting the ointment cool. These formulations were subjected to a comprehensive evaluation of their consistency, homogeneity, spreadability, viscosity, pH, drug content, UV absorbance, FTIR,DSC, and XRD study conducted. In addition to utilizing dialysis cellulose membrane, an in vitro study was carried out using Franz cells. Very well physicochemical properties were demonstrated by every synthesized composition. According to FTIR, SEM and XRD studies, the active ingredient (piroxicam salt) and additives used as drug permeation enhancers (oils) did not exhibit any physicochemical incompatibilities. The maximal release of the F4 thymol enhancer formulation was 69.183%. The current study found that the topical ointment of Piroxicam salt can be more permeable when it contains thymus oil >DNSO>clove oil >and castor oil